Oxygen derived free radicals in patients with chronic pancreatic and other digestive diseases. Issue 5 (May 1990) - Basso, D; Panozzo, M P; Fabris, C; del Favero, G; Meggiato, T; Fogar, P; Meani, A; Faggian, D; Plebani, M; Burlina, A
Abstract : To ascertain modifications in the activation products derived from oxygen free radicals in patients with chronic pancreatic and extra-pancreatic diseases, lipid peroxide activity was measured in the sera of 40 control subjects, 28 patients with pancreatic cancer, 49 with chronic pancreatitis, and 53 with extra-pancreatic diseases. In 142 of the subjects, elastase 1, amylase, and pancreatic isoamylase activities were also determined. Increased lipid peroxide activities were found in some patients with both chronic pancreatic and extra-pancreatic diseases. Patients with chronic pancreatitis studied during relapse had higher activities of lipid peroxides than those without active disease. No difference was found between the values in patients with pancreatic cancer with liver metastases and those without. Correlations were found between lipid peroxides and both amylase and pancreatic isoamylase activities; no correlation was detected between lipid peroxides and elastase 1. In benign biliary tract disease a correlation was detected between lipid peroxides and alanine aminotransferase and alkaline phosphatase activities. In all patients, however, a correlation was found between alkaline phosphatase and lipid peroxide activities. It is concluded that activation of oxygen derived free radicals occurs in chronic pancreatic as well as in extra-pancreatic disease; it seems to reflect the degree of inflammation.